Influence of Genetic Ancestry on INDEL Markers of NFKβ1, CASP8, PAR1, IL4 and CYP19A1 Genes in Leprosy Patients. - Pablo Pinto; Claudio Salgado; Ney Pereira Carneiro Santos; Sidney Santos; Ândrea Ribeiro- (Public Library of Science (PLoS), 2015)
BACKGROUND:Leprosy is an insidious infectious disease caused by the obligate intracellular bacteria Mycobacterium leprae, and host genetic factors can modulate the immune response and generate distinct categories of leprosy susceptibility that are also influenced by genetic ancestry. METHODOLOGY/PRINCIPAL FINDINGS:We investigated the possible effects of CYP19A1 [rs11575899], NFKβ1 [rs28362491], IL1α [rs3783553], CASP8 [rs3834129], UGT1A1 [rs8175347], PAR1 [rs11267092], CYP2E1 [INDEL 96pb] and IL4 [rs79071878] genes in a group of 141 leprosy patients and 180 healthy individuals. The INDELs were typed by PCR Multiplex in ABI PRISM 3130 and analyzed with GeneMapper ID v3.2. The NFKβ1, CASP8, PAR1 and IL4 INDELs were associated with leprosy susceptibility, while NFKβ1, CASP8, PAR1 and CYP19A1 were associated with the MB (Multibacilary) clinical form of leprosy. CONCLUSIONS/SIGNIFICANCE:NFKβ1 [rs28362491], CASP8 [rs3834129], PAR1 [rs11267092] and IL4 [rs79071878] genes are potential markers for susceptibility to leprosy development, while the INDELs in NFKβ1, CASP8, PAR1 and CYP19A1 (rs11575899) are potential markers for the severe clinical form MB. Moreover, all of these markers are influenced by genetic ancestry, and European contribution increases the risk to leprosy development, in other hand an increase in African contribution generates protection against leprosy.